Allochthonous particulate organic carbon in blue carbon ecosystems: Implications for accounting, stability, and policy - Anirban Akhand; Inés Mazarrasa; Stacey M. Trevathan-Tackett; K.M.G. Mostofa; Abhra Chanda; Hongbin Liu; Hiroshi Sakugawa; Si-Liang Li; Cong-Qiang Liu; Catherine E. Lovelock; Paul Lavery; Hilary Kennedy; et al. (Journal of Environmental Management, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Stablizing metal grid electrode by deep eutectic electrolyte for long-term electrochromic smart windows - Xiaolan Li; Zhiwei Chen; Jinyu Zhou; Yuchen Meng; Xueqing Tang; Kejia Zhang; Hongbin Zhao; Zhenyong Wang; Zhenzhong Yong; Laura Maggini; Davide Bonifazi; Zhigang Zhao; et al. (Chemical Engineering Journal, 2026)

3D magnetotelluric imaging of lithospheric magmatic systems in the Yitong Volcanic Area, Northeast China: Implications for fault-zone segmentation and seismic rupture dynamics along the Yilan-Yitong Fault - Cong Cao; Lingqiang Zhao; Yan Zhan; Yanfu Qi; Xiangyu Sun; Xiong Yang; Hongbin Lv; Qingliang Wang; Bowen Hou; Wenwen Qi (Tectonophysics, 2026)

Catalytic selective production of mono-aromatics from low-density polyethylene via HNO3-induced surface oxidation of activated carbon - Xiaona Lin; Xiaojie Zhuansun; Zhen Sun; Hongtao Li; Hongbin Cong (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method” [J. Clean. Product. 475 (2024) 143725] - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jiafa Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jia Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Terahertz Irradiation Improves Cognitive Impairments and Attenuates Alzheimer’s Neuropathology in the APPSWE/PS1DE9 Mouse: A Novel Therapeutic Intervention for Alzheimer’s Disease - Jun Zhang; Yixin Chen; Yarui Zhao; Panpan Wang; Hongbin Ding; Cong Liu; Junhong Lyu; Weidong Le (Neuroscience Bulletin, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the deposition of amyloid-β (Aβ), neurofibrillary tangles, neuroinflammation, and neurodegeneration in the brain. In recent years, considering the unsatisfied benefits of pharmacological therapies, non-pharmacological therapy has become a research hotspot for AD intervention. Terahertz (THz) waves with a range between microwave and infrared regions in the electromagnetic spectrum and high permeability to a wide range of materials have great potential in the bioengineering field. However, its biological impacts on the central nervous system, under either physiological or pathological conditions, are poorly investigated. In this study, we first measured the 0.14 THz waves penetration across the skull of a C57BL/6 mouse and found the percentage of THz penetration to be ~70%, guaranteeing that THz waves can reach the relevant brain regions. We then exposed the APP SWE /PS1 DE9 mouse model of AD to repeated low-frequency THz waves on the head. We demonstrated that THz waves treatment significantly improved the cognitive impairment and alleviated AD neuropathology including Aβ deposition and tau hyperphosphorylation in the AD mice. Moreover, THz waves treatment effectively attenuated mitochondrial impairment, neuroinflammation, and neuronal loss in the AD mouse brain. Our findings reveal previously unappreciated beneficial effects of THz waves treatment in AD and suggest that THz waves may have the potential to be used as a novel therapeutic intervention for this devastating disease.

Elevating sensing capability via dual-atom catalysts boosted luminol cathodic electrochemiluminescence - Yan-Chen Kong; Dan-Ling Wang; Jing-Jing Zhang; Yu-Xin Yang; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2024)

Single-atom boosted electrochemiluminescence via phosphorus doping of Fe–N/P–C catalysts - Yu-Xin Yang; Qian-Nan He; Cong-Hui Xu; Rida Javed; Hongbin Zhao; Daixin Ye; Wei Zhao (Analytica Chimica Acta, 2023)

Retraction Note to: Aneuploidy analysis of non-pronuclear embryos from IVF with use of array CGH: a case report - Deng Lixin; Xiang Zhifeng; He Cong; Zhang Jinzhou; Xie Hongbin (Journal of Molecular Histology, 2016)

RETRACTED ARTICLE: Aneuploidy analysis of non-pronuclear embryos from IVF with use of array CGH: a case report - Deng Lixin; Xiang Zhifeng; He Cong; Zhang Jinzhou; Xie Hongbin (Journal of Molecular Histology, 2014)

APRIL depletion induces cell cycle arrest and apoptosis through blocking TGF-β1/ERK signaling pathway in human colorectal cancer cells - Feng Wang; Lin Chen; Hongbin Ni; Guihua Wang; Weifeng Ding; Hui Cong; Shaoqing Ju; Shumei Yang; Huimin Wang (Molecular and Cellular Biochemistry, 2013)